The darkest minds [compact disc, unabridged] - Bracken, Alexandra (Bracken, Alexandra. Darkest minds, 2013)
Sixteen year old Ruby has spent the last six years in a government 'rehabilitation camp', a victim of the Kid-Killer virus that leaves any survivors with dangerous powers they cannot control. After escaping, she joins forces with a small tribe of other escapees on the run.